PENINGKATAN KEKUATAN LENTUR PRODUK 3D PRINTING BERBAHAN PETG DENGAN OPTIMASI PARAMETER PROSES MENGGUNAKAN METODE TAGUCHI - Riza, Eduar Iqbal; Budiyantoro, Cahyo; Nugroho, Aris Widyo (Media Mesin: Majalah Teknik Mesin, 2020)
Optimization of 3D printing process parameters with PETG material to the flexural strength response using the Taguchi method has been carried out. This study uses L9 (33) orthogonal arrays experimental design using three process parameters, namely nozzle temperature, extrusion width, and feed rate  with three levels in each parameter (240 ° C, 245 ° C, 250 ° C, 0.3 mm 0.35mm, 0.4mm, 50%, 75%, 100%). Specimens were prepared according to ISO 178: 2010 Standard using a Prusa-i3 3D printer. Following this their dimensions, mass, production time, and flexural strength were examined. The flexural strength response was analyzed using the Taguchi method via SN Ratio and ANOVA analysis to obtain the optimal parameters. The results showed that the most influential process parameters on the response of flexural strength respectively were the nozzle temperature, extrusion width and feed rate with an optimal combination of parameters namely nozzle temperature (250 ° C), extrusion width (0.35 mm), and feed rate (75%). The confirmation experiments showed that the optimal parameter combination obtained the highest flexural strength with a smaller data deviation (52.98 ± 0.65 MPa). In addition, all products being produced posses dimensions according to the standards used.